Comparative Analysis of Thermal Retention Capacity of Ice Chest Wood Cooler Stands Made from Pinus Caribeae and Nauclea Diderichii - E. A, Adelusi; K. O, Olaoye; K. S, Aina; O. O, Ajala; O. A, Adegoke (Journal of Forests, 2021)
The efficacy of a cooler or ice chest is measured by its preservative potentials, and how long it can make substance such as food and drinks remain hot/cold. In ensuring that an ice chest meets up to its expectation, this work investigated the construction, thaw rate and heat retention capacity of an ice chest cooler stands made from Pinus caribeae and Nauclea diderichii wood, with a view of improving its ability to maintain hotness/coldness of any substance stored in it for a longer period of time. The wood samples were machined and fabricated into a cooler stand in which plastic coolers were placed. 10kg mass of Ice block (0oC) and hot water (100oC) were used for the two tests considered in this study. Meanwhile, an ordinary cooler was used as a control. Weight reduction and thermometer were used to measure the thaw rate of the ice block and temperature loss of the water. For the ice block test, 6kg (1.8oC), 5kg (0.20oC) and 3kg (0.22oC) of ice block were left after 8 hours, while for the hot water test, water temperatures were 45oC, 25oC and 18oC after 12 hours for ice chest made from N. diderichi, P. caribaea and control respectively. The thaw rate and temperature loss was lowest for ice chest made with N. diderichi, thus implying that N. diderichi wood is a better choice for making wooden cooler stand. This study thus confirms that wood can be used to improve thermal retention capacity of ice chest cooler.